Computer vision -- ECCV 2016. 14th European Conference, Amsterdam, the Netherlands, October 11-14, 2016, Proceedings /: 14th European Conference, Amsterdam, the Netherlands, October 11-14, 2016, Proceedings. Part III : (2016) - Unknown
No abstract available